2022
DOI: 10.3390/cancers14020447
|View full text |Cite
|
Sign up to set email alerts
|

Novel Risk Classification Based on Pyroptosis-Related Genes Defines Immune Microenvironment and Pharmaceutical Landscape for Hepatocellular Carcinoma

Abstract: Growing evidence has indicated that pyroptosis functions in the development of cancer. Nonetheless, specific roles of pyroptosis-related genes in tumor progression, immune response, prognosis, and immunotherapy have not been thoroughly elucidated. After a comprehensive evaluation of pyroptosis genes, unsupervised clustering was performed to generate three distinct clusters from hepatocellular carcinoma (HCC) samples. Three distinct pyroptosis-related molecular subtypes comprising three gene clusters that had d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The expression level of the 5 proteins in HCC. such as pyroptosis and immunization activities, have shown advantages in predicting the prognosis of HCC (12,(14)(15)(16)24). A robust prediction model may help improve outcomes of HCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression level of the 5 proteins in HCC. such as pyroptosis and immunization activities, have shown advantages in predicting the prognosis of HCC (12,(14)(15)(16)24). A robust prediction model may help improve outcomes of HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…HCC is the most common type of all primary liver cancer with a poor prognosis. Gene risk models based on specific cell activities, such as pyroptosis and immunization activities, have shown advantages in predicting the prognosis of HCC ( 12 , 14 16 , 24 ). A robust prediction model may help improve the outcomes of HCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, nonstromal hepatocytes contribute significantly to shaping the tumor microenvironment, with macrophages attracting particular research interest. A study revealed a substantial association between pyroptosis and prognosis in HCC, suggesting that cellular pyroptosis-related genes contribute to the tumor microenvironment’s heterogeneity [ 127 ]. Utilizing in vivo macrophage depletion assays and in vitro analyses, researchers demonstrated the critical role of macrophages in mediating anti-tumor effects and identified a strong interdependence between macrophages and NK cells in efficiently eliminating tumor cells.…”
Section: Effect Of Macrophage Pcd On Liver Diseasementioning
confidence: 99%